In the Watches of the Night : Life in the Nocturnal City, 1820-1930. - Baldwin, Peter C., 1962- (Historical studies of urban America., 2011)
Before skyscrapers and streetlights glowed at all hours, American cities fell into inky blackness with each setting of the sun. But over the course of the nineteenth and early twentieth century, new technologies began to light up streets, sidewalks, buildings, and public spaces. Peter C. Baldwin's evocative book depicts the changing experience of the urban night over this period, visiting a host of actors - scavengers, newsboys, and mashers alike - in the nocturnal city. Baldwin examines work, crime, transportation, and leisure as he moves through the gaslight era, exploring the s.